A vacinação como tema de educação em saúde: Relato de experiência do projeto PET-Saúde - Júlia Barbosa Mangili; Ana Claudia Rodrigues Candido; Rafael Amaral Oliveira; Luciane Bisognin Ceretta; Renan Ceretta; Ioná Vieira Bez Birolo; Letícia Felipe Milak (Universidade Federal da Fronteira Sul, 2023)
O projeto de extensão da Universidade do Extremo Sul Catarinense denominado "Vivências e experiências na realidade da gestão e da assistência na atenção primária em saúde de Criciúma/SC", em parceria com o Ministério da Saúde, conta com a imersão do acadêmico no ensino, na pesquisa, na extensão universitária e na participação social. O presente relato de experiência visa descrever as ações de conscientização acerca da importância da vacinação realizadas em um município de do extremo sul catarinense, pelo grupo de Educação em Saúde, do programa PET-Saúde. As experiências foram apresentadas em quatro momentos: escolha da "vacinação" como tema de educação em saúde a ser abordado com a população; pesquisas sobre o tema e definição das ações a serem realizadas; organização e desenvolvimento dos materiais; e realização das ações. As ações de educação em saúde acerca da vacinação possibilitaram aos acadêmicos um processo de imersão teórico-prático dentro da atenção primária em saúde do município, desenvolvendo ações para trabalhar fragilidades apresentadas nesse nível de assistência. A educação em saúde é uma importante ferramenta para a prevenção e promoção da saúde. A vivência dentro do Sistema Único de Saúde contribui para a formação acadêmica e profissional dos estudantes da área da saúde, estimulando uma visão mais ampla sobre as condições enfrentadas nesse sistema. Palavras-chave: Imunização; Atenção Primária Em Saúde; Extensão Universitária Vaccination as a health education topic: Experience report from the PET-Saúde project Abstract:  The extension project of the University of Extremo Sul Catarinense, entitled "Experiences and realities in the management and primary health care assistance in Criciúma" (Santa Catarina State, Brazil), in partnership with the Ministry of Health, involves the immersion of students in teaching, research, university extension, and social engagement. This experiential report aims to describe the awareness-raising actions regarding the importance of vaccination in a municipality in the southernmost region of Santa Catarina by the Health Education group of the PET-Saúde program. The experiences were presented in four stages: selection of "vaccination" as the topic for health education with the population; research on the subject and definition of the actions to be carried out; organization and development of materials; and implementation of the actions. The health education activities on vaccination allowed the students to engage in a theoretical and practical immersion within the primary health care of the municipality, addressing weaknesses observed at this level of care. Health education is an essential tool for prevention and health promotion. The experience within the Unified Health System contributes to the academic and professional development of students in the health field, stimulating a broader understanding of the conditions faced within this system. Keywords: Immunization; Primary Health Care; University Extension